2020
DOI: 10.3389/fpsyg.2020.01769
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effect of Family Support on the Mediated Relation Between Negative Life Events and Antisocial Behavior Tendencies via Self-Esteem Among Chinese Adolescents

Abstract: Adolescents are particularly prone to antisocial behavior. The promoting effect of negative life events on antisocial behavior has been well-documented. However, the internal influence mechanisms between negative life events and antisocial behavior tendencies in adolescents are still unknown. The aim of this study was to explore the mediation effect of self-esteem and the moderated mediation effect of family support between negative life events and antisocial behavior tendencies in 8,958 adolescents who were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Therefore, it is possible that the observed decrease in influence in the antisocial condition is driven by common elements in both training programmes. For example, both training programmes focus on building self‐esteem and cultivating kindness and gratitude, which are associated with less antisocial behaviour (Bono et al, 2019 ; Donnellan et al, 2005 ; Gao et al, 2020 ). It is possible that cultivating kindness, gratitude and increasing self‐esteem as a result of undergoing one or the other of the programmes led to a reduction in social influence in the antisocial condition.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that the observed decrease in influence in the antisocial condition is driven by common elements in both training programmes. For example, both training programmes focus on building self‐esteem and cultivating kindness and gratitude, which are associated with less antisocial behaviour (Bono et al, 2019 ; Donnellan et al, 2005 ; Gao et al, 2020 ). It is possible that cultivating kindness, gratitude and increasing self‐esteem as a result of undergoing one or the other of the programmes led to a reduction in social influence in the antisocial condition.…”
Section: Discussionmentioning
confidence: 99%
“…Lin (2014) found that family support could significantly reduce the burnout of medical staff. There are also some studies exploring the moderating effect of family support ( Gao et al, 2020 ; Li et al, 2020 ). The COVID-19 could cause a dysfunctional level of anxiety among nurses.…”
Section: Introductionmentioning
confidence: 99%